Sexual Relationships of Elderly Males Who Have Lost Their Spouses - Nakahara, Yumiko (ANIMA Indonesian Psychological Journal, 2010)
This paper focuses on the sexual behavior and view of the 60-70’s age. The author investigate how an intimate relation with the opposite sex is formed, and how they act in their life, what kind of meaning of the opposite sex friend exist on their life. Subjects were three men over sixty living in suburban Tokyo and Osaka who lost their spouses and stayed widowers since, but having sexual relationships at present. Data were collected through a semi-structured interviewing and observation. Results reveal that though the subjects realize a diminishing physical function, they refuse to accept the negative labeling regarding their mental condition. Having a relationship with the current partners is like having a pseudo-marriage, bringing high spirits and a feeling of happiness. Sexuality functions as a realization of their masculinity as well as bringing them physical pleasure; the existence of a female partner could also help elevate their self-esteem. Artikel ini mencermati perilaku seksual dan pandangan mereka yang berusia 60-70-an. Penulis meneliti bagaimana hubungan mesra dengan lawan jenis terbentuk dan bagaimana mereka berperilaku dalam kehidupannya, dan apa makna keberadaan teman lawan jenisnya tersebut. Para subjek adalah tiga duda berusia di atas 60-an yang kehilangan istrinya dan tetap menduda, namun memiliki hubungan seksual saat ini. Data diperoleh melalui wawancara semi-terstruktur dan observasi. Hasil-hasil mengungkapkan bahwa para subjek yang walaupun mengakui mengalami kemunduran fisik, namun mereka menyangkal pelabelan negatif yang dikanakan terhadap kondisi mentalnya. Memiliki hubungan dengan mitranya dirasakan sebagai pseudo-pernikahan yang mampu mempertahankan semangatnya dan menimbulkan rasa senang. Seks berfungsi juga sebagai realitas kejantanannya sekaligus memberikan kenikmatan jasmaniah; adanya mitra perempuan juga meningkatkan rasa percaya dirinya.